Comparison of bacterial community structure and potential functions in hypoxic and non-hypoxic zones of the Changjiang Estuary. - Dong-Mei Wu; Qiu-Ping Dai; Xue-Zhu Liu; Ying-Ping Fan; Jian-Xin Wang (PLoS ONE, 2019)
Bacterioplankton play a key role in the global cycling of elements. To characterize the effects of hypoxia on bacterioplankton, bacterial community structure and function were investigated in the Changjiang Estuary. Water samples were collected from three layers (surface, middle, and bottom) at ten sampling sites in the Changjiang Estuary hypoxic and non-hypoxic zones. The community structure was analyzed using high-throughput sequencing of 16S rDNA genes, and the predictive metagenomic approach was used to investigate the functions of the bacterial community. Co-occurrence networks are constructed to investigate the relationship between different bacterioplankton. The results showed that community composition in hypoxic and non-hypoxic zones were markedly different. The diversity and richness of bacterial communities in the bottom layer (hypoxic zone) were remarkably higher than that of the surface layer (non-hypoxic). In the non-hypoxic zone, it was found that Proteobacteria, Bacteroidetes, and Flavobacteriia were the dominant groups while Alphaproteobacteria, SAR406 and Deltaproteobacteria were the dominant groups in the hypoxic zone. From the RDA analysis, it was shown that dissolved oxygen (DO) explained most of the bacterial community variation in the redundancy analysis targeting only hypoxia zones, whereas nutrients and salinity explained most of the variation across all samples in the Changjiang Estuary. To understand the genes involved in nitrogen metabolism, an analysis of the oxidation state of nitrogen was performed. The results showed that the bacterial community in the surface layer (non-hypoxic) had more genes involved in dissimilatory nitrate reduction, assimilatory nitrate reduction, denitrification, and anammox, while that in the middle and bottom layers (hypoxic zone) had more abundant genes associated with nitrogen fixation and nitrification. Co-occurrence networks revealed that microbial assemblages in the middle and bottom layers shared more niche spaces than in the surface layer (non-hypoxic zone). The environmental heterogeneity in the hypoxic and non-hypoxic zones might be important environmental factors that determine the bacterial composition in these two zones.